The Value of H-1B Status in Times of Scarcity - Chad Sparber (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
For-profit firms are limited in their ability to hire new, foreign-born, highly-educated workers after quotas on H-1B work permits are met each year, though they are able to hire existing H-1B workers. Universities and other non-profit research institutions do not face the same restrictions. Using difference in- difference methodology, this paper estimates the marginal value of an accepted H-1B job offer - in the form of wages - at for-profit firms after quotas have been met. Lower-bound estimates suggest a 1% wage premium with the largest differences occurring in the first month after meeting the quota. At least some of these effects are attributable to wage increases within narrowly-defined groups of workers during years in which available H-1B permits are quickly exhausted. These results provide indirect evidence that H-1B workers are imperfectly substitutable with other labor sources.
Keywords: J61; F22; 330; Skilled Workers; H-1B Work Permit; Immigration; Difference-in-Difference